Lithium ion battery negative electrode and manufacturing method thereof
By using silicon nanoparticles bound to carbon atoms in the negative electrode of lithium-ion batteries to form a three-dimensional crosslinking network structure of Si-C bonds, the structural damage caused by volume changes during the charge and discharge cycle is solved, and the service life of the battery is significantly extended.
Patent Information
- Application Number
- CN202510029423.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The volume change in the negative electrode of lithium-ion battery during the charging and discharge cycle leads to structural damage and shortening of battery life, and existing methods have not fully solved these problems.
Silicon nanoparticles bound to carbon atoms are used to form a stable three-dimensional crosslinking network structure through click chemical reactions to form Si-C bonds to enhance the mechanical strength of the negative electrode.
It significantly enhances the mechanical strength of the negative electrode of the battery, avoids expansion and contraction problems during the cycle, extends the service life of the battery, and increases the number of charge and discharge cycles by 5 to 10 times.
Smart Images

Figure CN119742311A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage devices, specifically the field of lithium-ion batteries, and relates to the design and manufacture of negative electrodes of lithium-ion batteries to enhance the stability of the batteries during charging and discharging, thereby extending the service life of the batteries. Background Art
[0002] Lithium-ion batteries have attracted much attention due to their high energy density and higher safety performance than traditional lithium-ion batteries. However, a major challenge in the development of lithium-ion batteries is the mechanical integrity of the negative electrode. The negative electrode undergoes significant volume changes during the charge and discharge cycle, resulting in structural damage and shortened battery life. Existing methods have failed to fully address these problems, so an innovative method is urgently needed to enhance the durability and performance of the negative electrode.
[0003] Global demand for battery capacity is driven by the rapid growth of electric vehicles (EVs), renewable energy storage and consumer electronics. According to the International Energy Agency (IEA), global battery demand is expected to increase 30 times between 2020 and 2030, reaching approximately 14,000 GWh by 2030. This surge is mainly attributed to the accelerated adoption of electric vehicles and the integration of renewable energy, which require efficient and scalable energy storage solutions.
[0004] Silicon is considered an ideal material for lithium-ion battery anodes due to its high theoretical capacity of about 4200 mAh / g (about ten times that of traditional graphite anodes). However, silicon anodes face significant technical challenges, mainly due to their volume expansion (up to 300%) during lithiation and delithiation cycles, which leads to the following problems: Mechanical degradation: Repeated expansion and contraction can cause severe mechanical stress, leading to cracking and pulverization of silicon particles, which can significantly reduce the cycle life of the battery; Loss of electrical contact: Mechanical degradation leads to loss of electrical contact between the silicon particles and the conductive matrix, reducing the capacity and efficiency of the battery over time; Solid electrolyte interface (SEI) layer instability: Continuous volume changes destroy the SEI layer, leading to increased electrolyte consumption and reduced Coulombic efficiency.
[0005] In summary, the present invention provides a lithium ion battery negative electrode and a method for manufacturing the same to solve the above problems. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lithium-ion battery negative electrode and a method for manufacturing the same. The advantages of the present invention are that silicon particles combined with carbon atoms are used to construct a stable three-dimensional network, and the formation of Si-C bonds is achieved through click chemistry reactions. This is an efficient and selective reaction that can form strong covalent bonds. The network significantly enhances the mechanical strength of the negative electrode and avoids expansion and contraction problems during the cycle.
[0007] To achieve the above object, the present invention provides the following technical solutions: A lithium ion battery negative electrode adopts silicon nanoparticles combined with carbon atoms to form a stable three-dimensional cross-linked network structure, and adopts carbon materials and silicon nanoparticles to form chemical bonds Si-C.
[0008] By adopting the above technical solution, the formation of Si-C bonds is achieved through click chemistry reaction, which is an efficient and selective reaction that can form strong covalent bonds. This network significantly enhances the mechanical strength of the negative electrode and avoids expansion and contraction problems during the cycle.
[0009] A method for manufacturing a negative electrode of a lithium ion battery comprises the following steps: Step 1: Preparation and manufacture of silicon particles; Step 2: Formation of a three-dimensional network of silicon-carbon bonding; Step 3: Characterize the successfully formed silicon-carbon three-dimensional network and the charge and discharge performance of its battery.
[0010] By adopting the above technical solution, the energy density, cycle life and safety of lithium-ion batteries can be significantly improved.
[0011] The present invention is further configured as follows: the preparation of silicon particles in step 1 includes preliminary etching, separation etching and ultrasonic treatment to generate particles, specifically including the following steps: Step S1, preliminary etching: the silicon wafer is placed in a mixed solution of hydrofluoric acid (HF) and ethanol (EtOH) for electrochemical etching; Step S2, separation etching: further etching the porous silicon by increasing the concentration of hydrofluoric acid and reducing the proportion of ethanol to separate it from the surface of the silicon wafer to form an independent porous silicon film; Step S3, ultrasonic treatment to generate particles: subjecting the separated porous silicon film to ultrasonic treatment to first decompose it into microparticles, and then continue ultrasonic treatment to generate silicon nanoparticles.
[0012] By adopting the above technical solution, it is convenient to convert silicon wafers into independent porous silicon films, and then process them into microparticles and nanoparticles.
[0013] The present invention is further configured as follows: the preliminary etching in step S1 specifically comprises the following steps: Step V1, cleaning: first, the silicon wafer is ultrasonically cleaned with isopropyl alcohol (IPA) for 15 minutes to remove surface impurities and oxides; Step V2, solution preparation: Mix 48% HF and ethanol in a volume ratio of 3:1. Ensure that the operation is carried out in a well-ventilated environment and follow the safe operating procedures; Step V3, electrode connection: connect the platinum electrode as cathode and the aluminum plate as anode to the electrochemical etching unit; Step V4, current application: set the current density to 90 mA / cm², for an effective etching area of 8.6 cm², the total current is 720 mA, and the etching lasts for 5 minutes.
[0014] By adopting the above technical solution, the preliminary etching work can be completed conveniently.
[0015] The present invention is further configured as follows: the separation etching in step S2 specifically includes the following steps: Step K1, solution replacement: using 48% HF and ethanol solution in a volume ratio of 1:29; Step K2, current application: Apply a current of 48 mA for secondary etching for 2 minutes to separate the porous silicon structure from the silicon wafer.
[0016] By adopting the above technical solution, the separation etching work can be completed conveniently.
[0017] The present invention is further configured as follows: the formation of the three-dimensional network of silicon-carbon bonding in step 2 includes the preparation of hydrogen-terminated silicon particles, microwave-assisted click chemistry and Si-C bond formation and the formation of the three-dimensional network, specifically including the following steps: Step L1, preparation of hydrogen-terminated silicon particles: functionalizing silicon particles through microwave-assisted hydrosilation reaction to generate reactive groups such as hydrogen, alkyl or carboxylic acid; Step L2, microwave-assisted click chemistry and Si-C bond formation: using microwave radiation high-efficiency technology to promote the formation of Si-C covalent bonds under mild conditions; Step L3, formation of a three-dimensional network: Si-C bonded nanoparticles are constructed into a three-dimensional network through self-assembly and further cross-linking chemical reactions.
[0018] By adopting the above technical solution, a stable Si-C three-dimensional network can be easily constructed to improve the mechanical strength and conductive properties of the electrode material.
[0019] The present invention is further configured as follows: the microwave-assisted click chemistry and Si-C bond formation in step L2 specifically include the following steps: Step N1, microwave radiation to generate free radicals: After the silicon nanoparticles are pre-treated to form hydrogen end groups, they are then irradiated with microwave radiation to break the Si-H bonds and generate silicon free radicals (Si•); Step N2, reaction with olefins: Silicon radicals react rapidly with olefins (R-CH=CH2) to form Si-C bonds. The hydrogen radicals (H•) generated in this process can also react with olefins to further stabilize the Si-C bonds.
[0020] By adopting the above technical solution, the formation of Si-C covalent bonds can be promoted under mild conditions.
[0021] The present invention is further configured as follows: the formation of the three-dimensional network in step L3 specifically includes the following steps: Step M1, three-dimensional structure formation: Si-C bond particles can spontaneously organize into a three-dimensional structure through the interaction between particles; Step M2, structural cross-linking: introducing additional chemical cross-linking agents or further hydrosilation reactions to enhance the integrity of the network structure.
[0022] By adopting the above technical solution, the mechanical strength and electrical conductivity of the material are improved.
[0023] The present invention is further configured as follows: the characterization of the successfully formed silicon-carbon three-dimensional network and the charge and discharge performance of the battery thereof in step three specifically comprises the following steps: Step F1, silicon particle characterization: The size and morphology of silicon nanoparticles are analyzed by transmission electron microscopy (TEM) to confirm the consistency and crystal structure of the particles, the successful formation of Si-C bonds is verified by Fourier transform infrared spectroscopy (FTIR), and the optical properties and quantum confinement effects of silicon nanoparticles are evaluated by photoluminescence (PL) spectroscopy; Step F2, Si-C bonding characterization: FTIR test showed that all samples clearly presented Si-CH2 stretching vibration peaks, indicating the successful formation of Si-C bonds, and carbonyl and hydroxyl absorption peaks were observed, indicating that surface functionalization further enhanced the compatibility of the negative electrode material with the electrolyte.
[0024] By adopting the above technical solutions, the mechanical and electrochemical properties of Si-C bonding materials are verified, confirming their applicability in high-performance batteries.
[0025] In summary, the beneficial technical effects of the present invention are: The present invention uses silicon nanoparticles combined with carbon atoms to form a stable three-dimensional cross-linked network structure. By forming Si-C bonds, the mechanical strength of the battery negative electrode is effectively improved, the volume expansion problem is alleviated, and the battery life is significantly extended. Compared with traditional batteries, the number of charge and discharge cycles of the battery can be increased by 5 to 10 times. This innovative method overcomes the main limitations of the prior art by combining the characteristics of mechanical strength and enhanced conductivity, and provides a feasible solution for the development of high-capacity, durable silicon-based lithium-ion batteries.
[0026] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 Schematic diagram of the manufacturing method of the present invention Figure 2 Schematic diagram of the failure mechanism of the silicon negative electrode during the charge and discharge process in the present invention; Figure 3 A schematic diagram of a three-dimensional network of silicon particles in a negative electrode of a battery formed by the method of the present invention; Figure 4 Schematic diagram of the preparation process of silicon particles for negative electrode of lithium ion battery in the present invention; Figure 5 It is a schematic diagram of a manufacturing device for forming silicon particles in the present invention; Figure 6 It is a schematic diagram of an etching unit used for forming silicon particles in the present invention, and specifically illustrates the formation of a porous silicon structure and its subsequent processing process; Figure 7 A schematic diagram of the Si-C cross-linking process achieved by "click chemistry" in the present invention, showing the key reaction mechanism for forming a three-dimensional network; Figure 8 A schematic diagram of the microwave-assisted hydrosilation reaction of the present invention, showing the process of generating free radicals on the silicon surface and how to form Si-C bonds in the presence of a hydrosilation agent (such as olefins and alkynes); Fig. 9 This is a high-resolution transmission electron microscope (TEM) image of the present invention, showing the uniform size and crystallinity of the prepared silicon nanoparticles, confirming the success of the synthesis process; Fig.10 : Left: FTIR spectrum showing the presence of Si-C and CH bonds, confirming the successful functionalization of silicon particles; Middle: FTIR spectrum, indicating characteristic peaks of silicon surface oxidation, including broad OH and Si-O-Si absorption peaks; Right: Photoluminescence (PL) spectrum showing the quantum confinement effect of silicon particles, emphasizing the uniformity of particle size; Fig.11 Comparison of spectra of three different samples (labeled as "a", "b", and "c") in the present invention, showing characteristic peaks of carbonyl (C=O) stretching vibration, Si-C bond formation, and hydroxyl (OH) stretching vibration; Fig.12 This is a structural comparison diagram of the traditional silicon negative electrode (left) and the silicon negative electrode strengthened by Si-C bonds (right) in the present invention when not under stress; Fig.13 This is a structural comparison diagram of the traditional silicon negative electrode (left) and the silicon negative electrode strengthened by Si-C bond (right) after 2000 bending tests in the present invention; Fig.14 The high capacity and long cycle stability of the present invention: the relationship between the specific capacity and the number of cycles of the silicon negative electrode at different current densities (10 A / g, 20 A / g and 40 A / g), showing that it can still maintain a capacity stability of about 800mAh / g after 1200 cycles at 10 A / g; Fig.15 The high rate and ultra-fast charging performance of the present invention: The electrochemical performance of the silicon negative electrode at different charging rates (0.5C to 50C): Above: The relationship between specific capacity and cycle number, indicating that the negative electrode can maintain stable performance under ultrafast charging conditions; The figure below shows the change of Coulombic efficiency with the number of cycles, showing that it can maintain a stable efficiency of more than 99% at different rates. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0029] The main summary of the current solution is as follows: a. Doping Method: Introduce carbon materials such as graphene, carbon nanotubes or amorphous carbon into the silicon anode to improve conductivity and mechanical strength.
[0030] Effectiveness: The carbon improves the electrical connection and provides a buffer for silicon’s volume changes, enhancing the overall structural integrity of the anode.
[0031] Limitations: Although carbon doping improves conductivity and alleviates the expansion problem to some extent, it cannot completely prevent the pulverization of silicon particles and the resulting long-cycle capacity decay.
[0032] b. Binders and polymers Methods: Binders such as polyvinylidene fluoride (PVDF) and carboxymethyl cellulose (CMC) were used to maintain the structural integrity of the silicon anode.
[0033] Effectiveness: Binders help accommodate volume changes and maintain mechanical strength by binding silicon particles to the current collector.
[0034] Limitations: Binders improve mechanical stability but offer limited enhancements to conductivity. They also add weight and complexity to the battery manufacturing process.
[0035] c. Si-X bond formation Method: Forming silicon compounds such as silicon oxide (SiOx) or silicon alloys (e.g. Si-Ti) to reduce expansion and improve structural integrity.
[0036] Effectiveness: Si-X compounds can alleviate some of the expansion issues and improve cycle life by providing a more stable matrix for lithium insertion.
[0037] Limitations: These modifications generally result in lower specific capacities than pure silicon and can increase the complexity of the manufacturing process. For example, Si-O bonds can lead to reduced conductivity.
[0038] d. Silicon Nanoparticles and Quantum Dots Methods: Use silicon nanoparticles or silicon quantum dots (SiQDs) to reduce the absolute volume change of each particle during lithiation.
[0039] Effectiveness: Smaller particles can better accommodate volume changes and reduce mechanical stress, thereby improving the cycling stability of the anode.
[0040] Limitations: Although this approach reduces powdering, nanoparticle aggregation and maintenance of electrical contact during long-term cycling remain challenging. Furthermore, the synthesis and handling of nanoparticles can be complex and expensive.
[0041] The invention discloses a negative electrode for a lithium ion battery. The negative electrode for the lithium ion battery adopts silicon nanoparticles combined with carbon atoms to form a stable three-dimensional cross-linked network structure, and adopts carbon materials and silicon nanoparticles to form chemical bonds Si-C.
[0042] Reference Figure 1-15 , is a method for manufacturing a negative electrode of a lithium ion battery disclosed in the present invention, the manufacturing method is applied to the negative electrode of the lithium ion battery as claimed in claim 1, comprising the following steps: Step 1: Preparation and manufacture of silicon particles; Step 2: Formation of a three-dimensional network of silicon-carbon bonding; Step 3: Characterize the successfully formed silicon-carbon three-dimensional network and the charge and discharge performance of its battery.
[0043] In this embodiment, the preparation of silicon particles in step 1 includes preliminary etching, separation etching and ultrasonic treatment to generate particles, which specifically includes the following steps: Step S1, preliminary etching: the silicon wafer is placed in a mixed solution of hydrofluoric acid (HF) and ethanol (EtOH) for electrochemical etching; Step S1 specifically includes the following steps: Step V1, cleaning: first, the silicon wafer is ultrasonically cleaned with isopropyl alcohol (IPA) for 15 minutes to remove surface impurities and oxides; Step V2, solution preparation: Mix 48% HF and ethanol in a volume ratio of 3:1. Ensure that the operation is carried out in a well-ventilated environment and follow the safe operating procedures; Step V3, electrode connection: connect the platinum electrode as cathode and the aluminum plate as anode to the electrochemical etching unit; Step V4, current application: set the current density to 90 mA / cm², for an effective etching area of 8.6 cm², the total current is 720 mA, and the etching lasts for 5 minutes.
[0044] Step S2, separation etching: further etching the porous silicon by increasing the concentration of hydrofluoric acid and reducing the proportion of ethanol to separate it from the surface of the silicon wafer to form an independent porous silicon film; Step S2 specifically includes the following steps: Step K1, solution replacement: using 48% HF and ethanol solution in a volume ratio of 1:29; Step K2, current application: Apply a current of 48 mA for secondary etching for 2 minutes to separate the porous silicon structure from the silicon wafer.
[0045] Step S3, ultrasonic treatment to generate particles: subjecting the separated porous silicon film to ultrasonic treatment to first decompose it into microparticles, and then continue ultrasonic treatment to generate silicon nanoparticles.
[0046] In this embodiment, the formation of the three-dimensional network of silicon-carbon bonding in step 2 includes the preparation of hydrogen-terminated silicon particles, microwave-assisted click chemistry and Si-C bond formation and the formation of the three-dimensional network, which specifically includes the following steps: Step L1, preparation of hydrogen-terminated silicon particles: functionalization of silicon particles by microwave-assisted hydrosilation reaction to generate reactive groups such as hydrogen, alkyl or carboxylic acid, wherein the hydrosilation reaction specifically comprises: treating silicon nanoparticles with a hydrogen-containing reagent or exposing them to hydrogen plasma, resulting in the formation of Si-H bonds, the reaction equation being: Si+H2→Si-HSi+H2→Si-H; Step L2, microwave-assisted click chemistry and Si-C bond formation: using microwave radiation high-efficiency technology to promote the formation of Si-C covalent bonds under mild conditions; Step L2 specifically includes the following steps: Step N1, microwave radiation to generate free radicals: After the silicon nanoparticles are pre-treated to form hydrogen end groups, they are then irradiated with microwave radiation to break the Si-H bonds and generate silicon free radicals (Si•); Step N2, reaction with olefins: Silicon radicals react rapidly with olefins (R-CH=CH2) to form Si-C bonds. The hydrogen radicals (H•) generated in this process can also react with olefins to further stabilize the Si-C bonds. Step L3, formation of a three-dimensional network: through self-assembly and further cross-linking chemical reactions, the Si-C bond nanoparticles are constructed into a three-dimensional network. Step L3 specifically includes the following steps: Step M1, three-dimensional structure formation: Si-C bond particles can spontaneously organize into a three-dimensional structure through the interaction between particles; Step M2, structural cross-linking: introducing additional chemical cross-linking agents or further hydrosilation reactions to enhance the integrity of the network structure.
[0047] In this embodiment, the characterization of the successfully formed silicon-carbon three-dimensional network and the charge and discharge performance of its battery in step 3 specifically includes the following steps: Step F1, silicon particle characterization: The size and morphology of silicon nanoparticles are analyzed by transmission electron microscopy (TEM) to confirm the consistency and crystal structure of the particles, the successful formation of Si-C bonds is verified by Fourier transform infrared spectroscopy (FTIR), and the optical properties and quantum confinement effects of silicon nanoparticles are evaluated by photoluminescence (PL) spectroscopy; Step F2, Si-C bonding characterization: FTIR test showed that all samples clearly presented Si-CH2 stretching vibration peaks, indicating the successful formation of Si-C bonds, and carbonyl and hydroxyl absorption peaks were observed, indicating that surface functionalization further enhanced the compatibility of the negative electrode material with the electrolyte.
[0048] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A negative electrode for a lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery adopts silicon nanoparticles combined with carbon atoms to form a stable three-dimensional cross-linked network structure, and adopts carbon materials and silicon nanoparticles to form chemical bonds Si-C.
2. A method for manufacturing a negative electrode of a lithium ion battery, characterized in that: The manufacturing method is applied to the lithium-ion battery negative electrode as claimed in claim 1, comprising the following steps: Step 1: Preparation and manufacture of silicon particles; Step 2: Formation of a three-dimensional network of silicon-carbon bonding; Step 3: Characterize the successfully formed silicon-carbon three-dimensional network and the charge and discharge performance of its battery.
3. The method for manufacturing a negative electrode of a lithium ion battery according to claim 2, characterized in that: The preparation of silicon particles in step 1 includes preliminary etching, separation etching and ultrasonic treatment to generate particles, and specifically includes the following steps: Step S1, preliminary etching: the silicon wafer is placed in a mixed solution of hydrofluoric acid (HF) and ethanol (EtOH) for electrochemical etching; Step S2, separation etching: further etching the porous silicon by increasing the concentration of hydrofluoric acid and reducing the proportion of ethanol to separate it from the surface of the silicon wafer to form an independent porous silicon film; Step S3, ultrasonic treatment to generate particles: subjecting the separated porous silicon film to ultrasonic treatment to first decompose it into microparticles, and then continue ultrasonic treatment to generate silicon nanoparticles.
4. The method for manufacturing a negative electrode of a lithium ion battery according to claim 3, characterized in that: The preliminary etching in step S1 specifically includes the following steps: Step V1, cleaning: first, the silicon wafer is ultrasonically cleaned with isopropyl alcohol (IPA) for 15 minutes to remove surface impurities and oxides; Step V2, solution preparation: Mix 48% HF and ethanol in a volume ratio of 3:
1. Ensure that the operation is carried out in a well-ventilated environment and follow the safe operating procedures; Step V3, electrode connection: connect the platinum electrode as cathode and the aluminum plate as anode to the electrochemical etching unit; Step V4, current application: set the current density to 90 mA / cm², for an effective etching area of 8.6 cm², the total current is 720 mA, and the etching lasts for 5 minutes.
5. The method for manufacturing a negative electrode of a lithium ion battery according to claim 3, characterized in that: The separation etching in step S2 specifically includes the following steps: Step K1, solution replacement: using 48% HF and ethanol solution in a volume ratio of 1:29; Step K2, current application: Apply a current of 48 mA for secondary etching for 2 minutes to separate the porous silicon structure from the silicon wafer.
6. The method for manufacturing a negative electrode of a lithium ion battery according to claim 2, characterized in that: The formation of the three-dimensional network of silicon-carbon bonding in step 2 includes the preparation of hydrogen-terminated silicon particles, microwave-assisted click chemistry and Si-C bond formation and the formation of a three-dimensional network, and specifically includes the following steps: Step L1, preparation of hydrogen-terminated silicon particles: functionalizing silicon particles through microwave-assisted hydrosilation reaction to generate reactive groups such as hydrogen, alkyl or carboxylic acid; Step L2, microwave-assisted click chemistry and Si-C bond formation: using microwave radiation high-efficiency technology to promote the formation of Si-C covalent bonds under mild conditions; Step L3, formation of a three-dimensional network: Si-C bonded nanoparticles are constructed into a three-dimensional network through self-assembly and further cross-linking chemical reactions.
7. The method for manufacturing a negative electrode of a lithium ion battery according to claim 6, characterized in that: The microwave-assisted click chemistry and Si-C bond formation in step L2 specifically include the following steps: Step N1, microwave radiation to generate free radicals: After the silicon nanoparticles are pre-treated to form hydrogen end groups, they are then irradiated with microwave radiation to break the Si-H bonds and generate silicon free radicals (Si•); Step N2, reaction with olefins: Silicon radicals react rapidly with olefins (R-CH=CH2) to form Si-C bonds. The hydrogen radicals (H•) generated in this process can also react with olefins to further stabilize the Si-C bonds.
8. The method for manufacturing a negative electrode of a lithium ion battery according to claim 6, characterized in that: The formation of the three-dimensional network in step L3 specifically includes the following steps: Step M1, three-dimensional structure formation: Si-C bond particles can spontaneously organize into a three-dimensional structure through the interaction between particles; Step M2, structural cross-linking: introducing additional chemical cross-linking agents or further hydrosilation reactions to enhance the integrity of the network structure.
9. The method for manufacturing a negative electrode of a lithium ion battery according to claim 2, characterized in that: The characterization of the successfully formed silicon-carbon three-dimensional network and the charge and discharge performance of the battery thereof in step 3 specifically includes the following steps: Step F1, silicon particle characterization: The size and morphology of silicon nanoparticles are analyzed by transmission electron microscopy (TEM) to confirm the consistency and crystal structure of the particles, the successful formation of Si-C bonds is verified by Fourier transform infrared spectroscopy (FTIR), and the optical properties and quantum confinement effects of silicon nanoparticles are evaluated by photoluminescence (PL) spectroscopy; Step F2, Si-C bonding characterization: FTIR test shows that all samples clearly present Si-CH2 The stretching vibration peak indicates the successful formation of Si-C bonds, and the carbonyl and hydroxyl absorption peaks are observed, indicating that the surface functionalization further enhances the compatibility of the negative electrode material with the electrolyte.
Citation Information
Patent Citations
Method for improving solar cell efficiency through luminous porous silicon particles
CN104795464A
Composite powder for use in an anode of a lithium ion battery, method for manufacturing a composite powder and lithium ion battery
CN107534139A
Preparation method of lithium ion battery negative electrode adhesive and method for preparing lithium ion battery negative electrode material
CN108899548A
Method for preparing lithium ion battery negative electrode binder, and method for preparing lithium ion battery negative electrode material
CN108933254A
Preparation method of carbon-coated porous silicon negative electrode material
CN111403694A